2021
DOI: 10.1158/2159-8290.cd-20-1588
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Evolution: How Bacteria and Cancer Cells Survive Stressful Conditions and Drug Treatment

Abstract: Summary: Cancer is characterized by loss of the regulatory mechanisms that preserve homeostasis in multicellular organisms, such as controlled proliferation, cell–cell adhesion, and tissue differentiation. The breakdown of multicellularity rules is accompanied by activation of “selfish,” unicellular-like life features, which are linked to the increased adaptability to environmental changes displayed by cancer cells. Mechanisms of stress response, resembling those observed in unicellular organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 106 publications
0
15
0
Order By: Relevance
“…On the one hand, Darwinian medicine has championed the idea that disease susceptibility is predisposed by macroevolutionary history [ 1 , 3 , 4 , 91 ]. Accordingly, studies of atavism and antagonistic pleiotropy provide clues for understanding tumor biology [ 22 , 28 , 33 ]. Herein, by building upon previous efforts [ 19 – 24 ], our meta-analyses across 13 cancer types demonstrated that the pan-cancer upregulation of UC genes involved in basic cellular machinery tends to promote tumor (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, Darwinian medicine has championed the idea that disease susceptibility is predisposed by macroevolutionary history [ 1 , 3 , 4 , 91 ]. Accordingly, studies of atavism and antagonistic pleiotropy provide clues for understanding tumor biology [ 22 , 28 , 33 ]. Herein, by building upon previous efforts [ 19 – 24 ], our meta-analyses across 13 cancer types demonstrated that the pan-cancer upregulation of UC genes involved in basic cellular machinery tends to promote tumor (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Phylostratigraphic or gene age analyses provide abundant supporting evidence: (1) cancer-related genes often emerge in unicellular (UC) ancestors or early metazoan (EM) ancestors [19][20][21][22]; (2) UC genes tend to be upregulated in tumors, while EM genes are often downregulated [23,24]. Therefore, atavism is increasingly accepted as a theoretical framework to understand cancer [4,[25][26][27] and adaptive mutability enabled by the ancient memory is even proposed as a target in tumor therapy [22,28]. On the other hand, natural selection may maximize the fitness in youth at the cost of promoting diseases of aging [3,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, even mutational processes have been linked to be at least partly modulated by the environment, as more evidence of adaptive mutability has been accumulated in unicellular and cancer cell populations [12, 13]. Epigenetic inheritance, phenotypic plasticity and other strictly non-genetic mechanisms which can create phenotypic diversity subject to selection further confound eco-evolutionary dynamics [14], thus calling for integration rather than separation of ecology and evolution.…”
Section: Introductionmentioning
confidence: 99%
“…63 Resistance to therapy could be innate or acquired. 64 Multiple studies have demonstrated the importance of clonal diversity and dynamics in resistance to therapeutic agents, 65 and the use of model systems like PTCs can be extremely useful in supporting clonal expansion studies about the process of acquired resistance. 46 Consider that in a typical clinical setting, large-scale molecular profiling of a patient's tumor can only be conducted for a few time points, i.e., when the tumor is surgically removed or when a biopsy is taken.…”
Section: Discussionmentioning
confidence: 99%